Sexual violence in conflict zones : from the ancient world to the era of human rights - Heineman, Elizabeth D., 1962- (Philadelphia : University of Pennsylvania Press, 2011)
From the publisher. Since the 1990s, sexual violence in conflict zones has received much media attention. In large part as a result of grassroots feminist organizing in the 1970s and 1980s, mass rapes in the wars in the former Yugoslavia and during the Rwandan genocide received widespread coverage, and international organizations -- from courts to NGOs to the UN -- have engaged in systematic efforts to hold perpetrators accountable and to ameliorate the effects of wartime sexual violence. Yet many millennia of conflict preceded these developments, and we know little about the longer-term history of conflict-based sexual violence. Sexual Violence in Conflict Zones helps to fill in the historical gaps. It provides insight into subjects that are of deep concern to the human rights community, such as the aftermath of conflict-based sexual violence, legal strategies for prosecuting it, the economic functions of sexual violence, and the ways perceived religious or racial difference can create or aggravate settings of sexual danger. Essays in the volume span a broad geographic, chronological, and thematic scope, touching on the ancient world, medieval Europe, the American Revolutionary War, precolonial and colonial Africa, Muslim Central Asia, the two world wars, and the Bangladeshi War of Independence. By considering a wide variety of cases, the contributors analyze the factors making sexual violence in conflict zones more or less likely and the resulting trauma more or less devastating. Topics covered range from the experiences of victims and the motivations of perpetrators, to the relationship between wartime and peacetime sexual violence, to the historical background of the contemporary feminist-inflected human rights moment. In bringing together historical and contemporary perspectives, this wide-ranging collection provides historians and human rights activists with tools for understanding long-term consequences of sexual violence as war-ravaged societies struggle to achieve postconflict stability.
Introduction: the history of sexual violence in conflict zones -- Rape in the American Revolution: process, reaction, and public re-creation / Sharon Block -- Sexual violence in the politics and policies of conquest: Amerindian women and the Spanish conquest of Alta California / Antonia I. Castañeda -- Femicide as terrorism: the case of Uzbekistan's unveiling murders / Marianne Kamp -- Girls, women, and the significance of sexual violence in ancient warfare / Kathy L. Gaca -- The victimization of women in late precolonial and early colonial warfare in Tanzania / James Giblin -- War crimes or atrocity stories? Anglo-American narratives of truth and deception in the aftermath of World War I / Nicoletta F. Gullace -- Sexual and nonsexual violence against "politicized women" in Central Europe after the Great War / Robert Gerwarth -- The "big rape": sex and sexual violence, war, and occupation in post-World War II memory and imagination / Atina Grossmann -- War as history, humanity in violence: men, women, and memories of 1971, East Pakistan/Bangladesh / Yasmin Saikia -- The theory and practice of female immunity in the medieval West / Anne Curry -- Law, war, and women in seventeenth-century England / Barbara Donagan -- "Unlawflly and against her consent": sexual violence and the military during the American Civil War / E. Susan Barber and Charles F. Ritter -- Legal responses to World War II sexual violence: the Japanese experience / Yuma Totani -- Toward accountability for violence against women in war: progress and challenges / Rhonda Copelon.
Includes bibliographical references and index.
In English.
Keywords: War victims -- History; War crimes -- History; Women -- Crimes against -- History; Women -- Violence against -- History; Women (International law); Women and war -- History; Rape as a weapon of war -- History; Political science -- Human Rights; Rape as a weapon of war; War crimes; War victims; Women and war; Women -- Crimes against; Women (International law); Women -- Violence against; Rape; Women in armed conflicts; Sex crimes; War victims; Gender-based violence; Sexual harassment; Human rights in armed conflicts; International law; Military history